1989
DOI: 10.1152/ajpendo.1989.256.1.e64
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid status on atrial natriuretic peptide release from isolated rat atria

Abstract: The effect of thyroid hormone on circulating levels of atrial natriuretic peptide (ANP) was studied in experimental hyperthyroid and hypothyroid rats. Plasma ANP was 102 +/- 5 pg/ml in euthyroid rats, 82 +/- 4 pg/ml in hypothyroid rats, and 138 +/- 11 pg/ml in hyperthyroid rats. We have also measured immunoreactive ANP in the atria of euthyroid, hypothyroid, and hyperthyroid rats. ANP content and concentration in the atria were lower (546 +/- 32 pg/mg tissue) in hyperthyroid rats than in hypothyroid rats (802 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The blood was taken into a prcehilled EDTA tube. To determine ANF secretion rate the right atrium was rapidly removed and superfused in a modi fied Langendorff apparatus as described before [10]. The atria were superfused with Tyrode solution at 0.5 ml/min for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…The blood was taken into a prcehilled EDTA tube. To determine ANF secretion rate the right atrium was rapidly removed and superfused in a modi fied Langendorff apparatus as described before [10]. The atria were superfused with Tyrode solution at 0.5 ml/min for 60 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hyperthyroidism causes an increase in atrial natriuretic peptide (ANP) secretion and a decreased release occurs in hypothyroid humans (143) and rats (144,145). Moreover, it has been reported that, in cultured rat atrial myocytes, T 3 stimulates both synthesis and release of ANP (146,147).…”
Section: Other Vasoactive Hormonesmentioning
confidence: 99%
“…Various studies have suggested the involvement of AT1 receptors in the expression of sodium appetite behavior using central administration of antagonists specific for these receptors (10)(11)(12). These alterations were revealed concomitantly with the observation of low genetic expression and reduced basal and stimulated release of atrial natriuretic peptide in hypothyroidism (9,13,14) together with the decreased capacity of proximal tubular sodium reabsorption (15). Literature data have led to the conclusion that the sodium appetite of hypothyroid rats is unique because it occurs in the presence of reduced plasma levels of both aldosterone and angiotensin II (3,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%